PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) DALAM KETERAMPILAN MENULIS KALIMAT SEDERHANA BAHASA JERMAN - Andira, Ayu; Hasmawati, Hasmawati; R, Mantasiah (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. This study aims to determine the application of the cooperative learning model type STAD. Planning, process and results of the STAD (Student Team Achievement Division) cooperative learning model in writing simple sentence skills in German for class X students of SMAN 2 Bulukumba. This research is a Classroom Action Research conducted with 2 cycles. The research data consists of two types, namely: qualitative data and quantitative data. Qualitative data were obtained through observation, while quantitative data were obtained through the test results of writing simple sentence skills in cycle I and cycle II. Data were analyzed using percentage techniques. The results showed that the skill of writing simple sentences with the percentage of scores obtained by students in the first cycle reached 56.55%, and the second cycle reached 64.62%. These results indicate that the application of the STAD (Student Team Achievement Division) cooperative learning model improves the simple sentence writing skills of class X students of SMAN 2 Bulukumba, Bulukumba Regency.